Localization of beta power decrease as measure for lateralization in pre-surgical language mapping with magnetoencephalography, compared with functional magnetic resonance imaging and validated by Wada test - Herfurth, Kirsten; Harpaz, Yuval; Roesch, Julie; Mueller, Nadine; Walther, Katrin; Kaltenhaeuser, Martin; Pauli, Elisabeth; Goldstein, Abraham; Hamer, Hajo; Buchfelder, Michael; Doerfler, Arnd; Prell, Julian; et al. (Frontiers in Human Neuroscience, 2022)
Objective: Atypical patterns of language lateralization due to early reorganizational processes constitute a challenge in pre-surgical evaluation of patients with pharmaco-resistant epilepsy. There is no consensus on an optimal analysis method used for the identification of language dominance in MEG. This study examines the concordance between MEG source localization of beta power desynchronization and fMRI with regard to lateralization and localization of expressive and receptive language areas using a visual verb generation task. Methods: Twenty-five patients with pharmaco-resistant epilepsy, including six patients with atypical language lateralization, and ten right-handed controls obtained MEG and fMRI language assessment. Fourteen patients additionally underwent Wada test. We analysed MEG beta power desynchronization in sensor (controls) and source space (patients and controls). Beta power decrease between 13-35 Hz was localized applying Dynamic Imaging of Coherent Sources beamformer technique. Statistical inferences were grounded on cluster-based permutation testing for single subjects. Results: Event related desynchronization of beta power in MEG was seen within the language dominant frontal and temporal lobe and within the premotor cortex. Our analysis pipeline consistently yielded left language dominance with high laterality indices in controls. Language lateralization in MEG and Wada test agreed in all 14 patients for inferior frontal, temporal and parietal language areas (Cohen’s Kappa=1, p<0.001). fMRI agreed with Wada test in 12 out of 14 cases (85.7%) for Broca’s area (Cohen’s Kappa=0.71, p=0.024), while agreement for temporal and temporo-parietal language areas were non-significant. Concordance between MEG and fMRI laterality indices was highest within the inferior frontal gyrus, with an agreement in 19/24 cases (79.2%), and non-significant for Wernicke’s area. Spatial agreement between fMRI and MEG varied considerably between subjects and brain regions with lowest Euclidean distances within the inferior frontal region of interest. Conclusion: Localizing the desynchronization of MEG beta power using a verb generation task is a promising tool for the identification of language dominance in pre-surgical evaluation of epilepsy patients. The overall agreement between MEG and fMRI was lower than expected and might be attributed to differences within the baseline condition. A larger sample size and an adjustment of the experimental designs are needed to draw further conclusions.